APPLICATION OF BLENDED LEARNING MODELS TO IMPROVE LEARNING INDEPENDENCE AND ACHIEVEMENT - Arsilawati Fahrulliah; Turdjai Turdjai (DIADIK, 2019)
The purpose of this study was to determine (1) Describe the application of Blended Learning to improve the independence of science learning students ;(2) Describe the application of Blended Learning can improve students' science learning achievement; (3) Describe the effectiveness of the application of Blended Learning in order to improve student learning achievementat SMP Negeri 10 Lahat. This research was conducted using classroom action research (CAR) and quasi-experimental research. Data collection methods in this study used observation sheets to measure the learning process and student learning independence and to measure learning achievement tests were used. This research was conducted in class IX E as a PTK class. This study produces conclusions: (1) the application of the blended learning model can improve student learning independence, (2) the application of the blended learning model can improve student achievement, (3) the application of the blended learning model effectively increases student learning achievement in science subjects